An entrepreneurial theory of the firm - Sautet, Frédéric E. (Foundations of the market economy series., 2000)
"An Entrepreneurial Theory of the Firm makes a thorough and comprehensive enquiry into the nature of the relationship that exists between firms and markets, with separate, in-depth explorations of both the existence and inner organization of the firm. Sautet develops a model that explains the emergence of the firm in the market process as the result of entrepreneurial activity in the context of genuine uncertainty and rivalrous competition. The Austrian angle enables him to provide a theory that is both alternative and complementary to established viewpoints."--Jacket